Investigating causes of data scattering about the prevalence of muscle and joint dysfunction of temporomandibular joints in dental patients - Boyan, Arkadiy; Bessonov, Vladimir (ScienceRise: Medical Science, 2017)
Aim of research. To study biopotentials of chewing muscles and possible noise phenomena in temporomandibular joints in dental patients, who have two and more symptoms of a muscle and joint dysfunction of a temporomandibular joint with no complaints for pains in chewing muscles at movements of a lower jaw as ones of criteria for substantiating appropriateness of setting the diagnosis of a temporomandibular joint dysfunction. Materials and methods. The group of 136 persons with 2,3,4 and more symptoms of a temporomandibular joint dysfunction, deviations in the work of the joint, but no complaints for pains at movements of a law jaw and chewing was formed of patients of the dental clinic. Results of research. The artrophonographic study demonstrated that patients with 2 and 3 symptoms related to a muscle and joint dysfunction of a temporomandibular joint, demonstrate disorders in the work of a temporomandibular joint (56,6% of patients) and ones with 4 and more symptoms – in 64,1%. The electromiographic study revealed the absence of disorders of biopotentials of chewing muscles in all 136 patients. Conclusions. One can make a conclusion that a muscle and joint dysfunction of a temporomandibular joint must not be diagnosed in these patients. The repeated examination, realized in 6 months proved the absence of worsening of a condition of chewing muscles and temporomandibular joint in such patients. Assessments of the prevalence of this disease, presented in literary sources, are overestimated unreasonably in a series of cases